Sudden cardiac death in inherited cardiomyopathy. (15th June 2017) - Collis, R.; Elliott, P.M.
Abstract: Cardiomyopathy is an important cause of sudden cardiac death particularly in adolescents and young adults. The risk of sudden cardiac death varies between individual cardiomyopathies and is dependent on the severity of disease, age and gender. Although rare in cardiomyopathies, a fundamental aspect of clinical management is a systematic and thorough clinical assessment to identify the small number of individuals who are at risk and who can be protected with prophylactic ICD therapy.